The Therapeutic Potential of the Anticancer Activity of Fucoidan: Current Advances and Hurdles - Jun-O. Jin; Pallavi Singh Chauhan; Ananta Prasad Arukha; Vishal Chavda; Anuj Dubey; Dhananjay Yadav (Marine Drugs, 2021)
Several types of cancers share cellular and molecular behaviors. Although many chemotherapy drugs have been designed to weaken the defenses of cancer cells, these drugs may also have cytotoxic effects on healthy tissues. Fucoidan, a sulfated fucose-based polysaccharide from brown algae, has gained much attention as an antitumor drug owing to its anticancer effects against multiple cancer types. Among the anticancer mechanisms of fucoidan are cell cycle arrest, apoptosis evocation, and stimulation of cytotoxic natural killer cells and macrophages. Fucoidan also protects against toxicity associated with chemotherapeutic drugs and radiation-induced damage. The synergistic effect of fucoidan with existing anticancer drugs has prompted researchers to explore its therapeutic potential. This review compiles the mechanisms through which fucoidan slows tumor growth, kills cancer cells, and interacts with cancer chemotherapy drugs. The obstacles involved in developing fucoidan as an anticancer agent are also discussed in this review.